Peningkatan Pemahaman Konsep Luas Bangun Datar Dengan Penerapan Guided Inquiry - Nabila Lugina Febinasari (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2019)
This research was intended to increase students‟ plane area concept understanding with the application of Guided Inquiry the students were 4th grader student of SDN Cisaat Rambay. This research employed classroom action research method with Kemmis and Taggart Model, which consisted of two cycles with two activities in each cycle. Each cycle consisted of four steps included planning, action, observation, reflection. The subject of this research were 4th grade students of SDN Cisaat Rambay which involved 40 students. The data collection technique used in this research were tes technique using pretest and posttest, and non-tes technique using observation of teacher‟s performance and student‟s activity. The data were analysed using both quantitative decriptive. The result of this research showed that before the treatment was conducted, the student‟s achievement of conceft understanding was about 10%. In cycle I, it was showed that the student‟s achievement of concept understanding was 57% which meant that there was 47% enchancement in compared with the result of pretest. In cycle II, it was showed that the students‟ achievement of concept understaning was 93%. This research concluded that the application of guided inquiry was able to increase 4th grade students‟ of concept understanding in learning plane shapes area.